2021
DOI: 10.1038/s41598-021-81597-7
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between fundus autofluorescence and visual function in patients with cone-rod dystrophy

Abstract: This study aimed to investigate the relationship between autofluorescence (AF) signal measured with ultra-wide field imaging and visual functions in patients with cone-rod dystrophy (CORD). A retrospective chart review was performed for CORD patients. We performed the visual field test and fundus autofluorescence (FAF) measurement and visualized retinal structures with optical coherence tomography (OCT) on the same day. Using binarised FAF images, we identified a low FAF area ratio (LFAR: low FAF/30°). Relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Diagnosis and treatment can therefore be delayed or mistaken until high sensitivity tests, such as FAF or OCT imaging, are promised [26][27] . Through collecting related data, Kanda et al [28] discovered a close connection between abnormalities in FAF and functional damage in CORD patients. Commonly, the small, circular areas of hypo-AF lesions in FAF were not notable on fundoscopy, with the hypo-AF lesions likely representing the RPE dysfunction of increased metabolic load due to photoreceptor apoptosis [26] .…”
Section: Cord With Crx In Chinese Patientsmentioning
confidence: 99%
“…Diagnosis and treatment can therefore be delayed or mistaken until high sensitivity tests, such as FAF or OCT imaging, are promised [26][27] . Through collecting related data, Kanda et al [28] discovered a close connection between abnormalities in FAF and functional damage in CORD patients. Commonly, the small, circular areas of hypo-AF lesions in FAF were not notable on fundoscopy, with the hypo-AF lesions likely representing the RPE dysfunction of increased metabolic load due to photoreceptor apoptosis [26] .…”
Section: Cord With Crx In Chinese Patientsmentioning
confidence: 99%
“…CORD patients present with decreased visual acuity (VA), impaired retinal sensitivity and color vision loss and sometimes demonstrate peripheral visual field loss at the end stage, followed by rod photoreceptor impairments [ 4 ]. Several studies have revealed a structure-function relationship in eyes with CORD, such as the correlation between VA and residual EZ and between retinal sensitivity and the abnormal autofluorescent area [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%